2008
DOI: 10.1051/0004-6361:200810540
|View full text |Cite
|
Sign up to set email alerts
|

New X-ray detections of Herbig stars

Abstract: Context. The interpretation of X-ray detections from Herbig Ae/Be stars is disputed as it is not clear whether these intermediate-mass pre-main sequence stars are able to drive a dynamo and ensuing phenomena of magnetic activity. Alternative X-ray production mechanisms, related to stellar winds, star-disk magnetospheres, or unresolved late-type T Tauri star companions have been proposed. Aims. The companion hypothesis can be tested by resolving Herbig stars in X-rays from their known visual secondaries. Furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 67 publications
7
47
0
1
Order By: Relevance
“…Carmona et al (2007) reported the detection of Hα emission and Li absorption in the K5Ve T Tauri companion. The companion is an X-ray source, and weaker X-ray emission is also detected from the position of the Herbig Ae/Be star (Stelzer et al 2009). The 10 μm silicate emission band shows rather pristine dust, while the SED points towards a flat disk, as reported by Meeus et al (2001).…”
Section: Stars With Measurements Suggestivementioning
confidence: 99%
See 3 more Smart Citations
“…Carmona et al (2007) reported the detection of Hα emission and Li absorption in the K5Ve T Tauri companion. The companion is an X-ray source, and weaker X-ray emission is also detected from the position of the Herbig Ae/Be star (Stelzer et al 2009). The 10 μm silicate emission band shows rather pristine dust, while the SED points towards a flat disk, as reported by Meeus et al (2001).…”
Section: Stars With Measurements Suggestivementioning
confidence: 99%
“…Preibisch et al (2006) derived an inclination of 58 • from MIDI/VLTI observations and found that the disk is very compact with an outer edge of ∼2.6 AU, potentially caused by a further, even closer, yet undetected companion. Recently, HD 144668 was for the first time resolved from its T Tauri companion in X-rays (Stelzer et al 2009). This observation showed that the bulk of the X-ray emission comes from the companion, but a weak source is associated with HD 144668 (or the hypothesized sub-arcsecond companion).…”
Section: Herbig Ae/be Stars With Detected Magnetic Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, especially peculiar Ap/Bp stars and young Herbig AeBe stars are prime candidates for being intrinsic X-ray emitters (e.g. Babel & Montmerle 1997;Stelzer et al 2009). In the Ap/Bp stars discussed here an interplay between stellar winds and large scale magnetic fields is thought to play the major role in the X-ray generation.…”
Section: Introductionmentioning
confidence: 99%